Multifactorial analysis of risk factors for foot ulcers in patients with neurovascular complications of diabetes - Fan, Zibo; Huang, Jinyan; Liu, Yue; Xie, Hao; Yang, Qinfeng; Liang, Yue; Ding, Hong (Frontiers in Endocrinology, 2024)
Background Diabetic foot ulcers (DFU) are a major complication associated with significant morbidity and mortality. While numerous studies have investigated risk factors for these ulcers in general, few have focused specifically on patients with Neurovascular Complications of Diabetes. This study aimed to evaluate the prevalence and risk factors for DFU in this specific population. Methods We analyzed data from the National Institutes of Health (NIS) database for the years 2017-2019, involving a cohort of 161,834 patients aged over 18 who were diagnosed with neurovascular complications of diabetes. Demographic characteristics (age, gender, ethnicity), hospital characteristics, comorbidities, and other relevant data were included for analysis. A binary logistic regression model was generated to identify independent risk factors for DFU. Results The prevalence of DFU among patients with neurovascular complications of diabetes was 29.4% during the period from 2017 to 2019. Compared to patients without DFU, those with DFU had longer hospitalization times and higher costs. The multiple regression analysis revealed that Iron-deficiency anemia (OR, 1.10; 95% CI, 1.01-1.11; P=0.019), Hypertension (OR, 1.07; 95% CI, 1.03-1.11; P=0.001), Obesity (OR, 1.08; 95% CI, 1.06-1.11; P<0.001), Peripheral vascular disorders (PVD) (OR, 1.69; 95% CI, 1.65-1.74; P<0.001), Osteomyelitis (OR, 7.10; 95% CI, 6.89-7.31; P<0.001), Tinea pedis (OR, 1.89; 95% CI, 1.59-2.26; P<0.001), Sepsis (OR, 1.24; 95% CI, 1.20-1.28; P<0.001), and onychomycosis (OR, 1.26; 95% CI, 1.13-1.42; P<0.001) were independent predictors for DFU in this population. Conclusion The study found a high prevalence of DFU in patients with neurovascular complications of diabetes. Identifying and addressing risk factors such as deficiency anemia, hypertension, obesity, PVD, infections, and foot conditions may contribute to reducing the prevalence of DFU in this vulnerable population.